ANALISIS KEPUASAN PENGGUNA SIM AKADEMIK UNIVERSITAS MENGGUNAKAN METODE EUCS - Irsyadunas Irsyadunas; Welsy Rahayu (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
The purpose of this research is to analyse and determine the influence of the dimensions of EUCS (content, accuracy, format, easy of use, and timeliness) to the satisfaction of students of the academic SIM in Sapta Mandiri University. This research was conducted by the survey method through the dissemination of a valid and reliable questionnaire to 98 active students in the Sapta Mandiri University. Sampling using total sampling techniques, the data obtained is then analyzed using multiple linear regression analyses. Data analysis results show that (1) a partial two-dimensional format and timeliness have a positive and significant influence on student satisfaction. While the three dimensions of content, accuracy, easy of use has no significant influence on customer satisfaction; (2) Simultaneously the content, accuracy, format, easy of use, and timeliness have a positive and significant influence on the user satisfaction of the academic SIM